Refined treatment response criteria for indolent systemic mastocytosis proposed by the ECNM-AIM consortium - Pyatilova, Polina; Akin, Cem; Alvarez-Twose, Iván; Arock, Michel; Bonadonna, Patrizia; Brockow, Knut; Butterfield, Joseph H.; Broesby-Olsen, Sigurd; Carter, Melody C.; Castells, Mariana; George, Tracy I.; Gotlib, Jason; et al. (The journal of allergy and clinical immunology. In practice, 2022)
Indolent systemic mastocytosis (ISM) has a favorable prognosis and normal life expectancy. However, many patients suffer from mast cell (MC) mediator-related symptoms, which significantly affect quality of life (QoL). Cutaneous, gastrointestinal, and neurological complaints, musculoskeletal pain, and the presence of skin lesions, anaphylaxis, and osteoporosis are the main symptoms and signs in ISM and must be assessed in all patients before and during treatment. Validated mastocytosis-specific patient-reported outcome measures (PROMs) should be used for this purpose. Serum tryptase and KIT D816V allele burden are recommended as secondary outcome parameters, noting that they do not reflect the severity of signs, symptoms, and related QoL impairment, but indirectly express MC burden. Changes from baseline of 90%, 60%, and 30% indicate complete response >90%, major response 60% to 90%, partial response 30% to 60%, and no response <30% to treatment. To conclude, we recommend the use of PROMs as primary outcome parameters to define treatment response in patients with ISM in clinical trials and in everyday clinical practice.